2021
DOI: 10.3390/ani11020310
|View full text |Cite
|
Sign up to set email alerts
|

Ecotyping of Anaplasma phagocytophilum from Wild Ungulates and Ticks Shows Circulation of Zoonotic Strains in Northeastern Italy

Abstract: Anaplasma phagocytophilum (A. phagocytophilum) is a tick-borne pathogen causing disease in both humans and animals. Human granulocytic anaplasmosis (HGA) is an emerging disease, but despite the remarkable prevalence in European ticks and wild animals, human infection appears underdiagnosed. Several genetic variants are circulating in Europe, including the zoonotic ecotype I. This study investigated A. phagocytophilum occurrence in wild ungulates and their ectoparasites in an area where HGA has been reported. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…To fully confirm this, however, it would be necessary to study the genetic variants of the pathogen. The obtained results are in agreement with previously published data in Europe [15,16,19,39,[41][42][43][44] based on which rather convincing molecular evidence was presented last year on ticks isolated from urban dogs [34].…”
Section: Discussionsupporting
confidence: 92%
“…To fully confirm this, however, it would be necessary to study the genetic variants of the pathogen. The obtained results are in agreement with previously published data in Europe [15,16,19,39,[41][42][43][44] based on which rather convincing molecular evidence was presented last year on ticks isolated from urban dogs [34].…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, due to the type of recruitment of roe deer (rescued animals) only blood was obtained, and no information about the possible presence of the parasite in other tissues may be obtained. Additionally, prevalence of A. phagocytophilum in other Italian regions showed higher prevalence rates in different wild ungulates [ 52 , 53 , 54 ], but the use of different molecular approaches could have influenced the outcoming results. Roe deer is considered to play an important role in spreading A. phagocytophilum [ 15 , 35 ], as it is also considered one of the major actors in the maintenance of I. ricinus populations [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, very recently, tick vectors, tick‐borne diseases and endoparasites have been studied in R. r. rupicapra but also the poorly investigated R. r. balcanica ; this research provided new insights into chamois parasitological status and tick infestation of the Balkan chamois (Yankov et al 2021). By combining parasitological and infectious disease studies, other authors also reported an unexpectedly high prevalence of tick‐borne A. phagocytophilum , including zoonotic strains, in Alpine chamois of the eastern Italian Alps (Grassi et al 2021). These two examples illustrate that chamois throughout Europe may harbor and suffer from known parasitological and viral diseases as well as those caused by emerging pathogens, such as tick‐borne pathogens; thus, increased and standardized screening is recommended wherever possible.…”
Section: Physiology and Diseasesmentioning
confidence: 97%